Implementasi Pengembangan Media Pembelajaran Menggunakan Aplikasi Benime Berbasis Problem Based Learning - Kadir, Dalimawaty; Dwi, Dara Fitrah; Sujarwo, Sujarwo; Friska, Novita (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to develop learning media using the Benime application integrated with the Problem Based Learning (PBL) model for the topic of changes in the states of matter at the elementary school level. The research was motivated by the lack of student engagement in learning activities and the prevailing teacher-centered approach. The study employed a Research and Development method using a modified ADDIE model that included three stages: analysis, design, and development. The resulting product, in the form of educational animated videos, was validated by content experts, media experts, and classroom teachers, achieving an average validation score of 84%, indicating a high level of feasibility. Benime facilitates engaging visualizations and interactivity, encouraging students to actively explore and solve problems. The originality of this research lies in the integration of Benime animation and the PBL model in science instruction at the elementary level which has not been widely applied. This research implies a significant potential for enhancing technology-based learning quality and fostering students’ active participation in knowledge construction.